PENGARUH PERMISSION EMAIL MARKETING TERHADAP PURCHASE INTENTION DAN DAMPAKNYA PADA PURCHASE DECISION (Survei Pada Customer Lazada Indonesia) - Harum, Jun Rachmawati; Kusumawati, Andriani; Kholid Mawardi, Muhammad (Profit: Jurnal Adminsitrasi Bisnis, 2021)
This study aims to discuss and test the role of permission email marketing that have an impact on purchase intention and purchase decision in the marketplace. Permission email marketing is one marketing tool that has many advantages, including the ability to reach a wider area and different market share but also the ability to make marketing deals with a small amount of investment. The researcher used the questionnaire as the primary data source given to 168 respondents, namely subscriber at Lazada Indonesia. The analytical tool used is Structural Equation Modeling Partial Least Squares (SEM-PLS) which is a causal modeling approach that aims to maximize the variance of latent variables which can be explained by predictor variables. The results showed that there was a strong influence between email marketing permissions with purchase intention and purchase decisions.